The Eye of The Falcon - Paver, Michelle (Gods and warriors ; 3., 2014)
Winter was colder than anyone can remember, and there is no spring. The eruption of Thalakrea has shrouded the sky in ash, and blotted out the Sun. Fate brings Hylas to the island of Keftiu. He is desperate to find his friends: Pirra, the daughter of the High Priestess, and Havoc the lion cub. But Keftiu has suffered more than anywhere from the fury of the gods, and the once-prosperous island has been ravaged by cold, famine and plague. As Hylas sets off alone, he is tormented by the fear that Pirra and Havoc may not have survived the winter...